Suspension of Duties as a Provisional Measure in a Disciplinary Procedure for Teaching Staff - de Vargas Cascales, María Cinta (Avances en Supervisión Educativa, 2025)
In a disciplinary sanctioning procedure, the suspension of the procedure, the suspension of the implicated official as a provisional measure, or both situations may occur. The suspension of a disciplinary procedure may be motivated by the need to obtain a prior judicial ruling, whose proven facts in a final judgment bind the Administration in the disciplinary sanctioning procedure. If the Administration, through its competent bodies, suspends an official from duties as a precautionary measure, it must adhere to a series of legal principles. The process of reasoned legal justification requires the competent authority to assess the indications, elements, and circumstances surrounding the adoption of the precautionary measure, granting it an appearance of legitimacy through the justification of adopting such restrictive measures and grounding this decision in legal causes. Furthermore, the decision must be legally argued by analyzing the potential damages and harm that may arise as a consequence of the delay in the final resolution.